Effect of Resonant Environment on Discrete Frequency Noise Generation from a Two-Dimensional Airfoil. Issue 1 (May 2021) - Yamada, K.; Furukawa, M.; Sakurada, S.; Mizokami, T.; Aso, S.; Sakoda, K.; Fukui, T.
Abstract: It is known that discrete frequency noise with specific peak frequency, which is often called tonal noise, is generated from an airfoil in the flow conditions within certain Reynolds number range. In this study, the tone noise generated from the NACA0012 airfoil inclined at a small angle to the stream is investigated. The test has been conducted in two different configurations to clarify the effect of resonant environment on the noise generation: one is a duct configuration in which wall was installed at both sides across the airfoil, and the other is a wall-free configuration without any wall around the airfoil. The numerical simulation with lattice Boltzmann method (LBM) also has been conducted to investigate detailed generation mechanism of the tone noise. The experimental results show that the tone noise is generated with several peak frequencies in the wall-free configuration, while it has a single peak for the duct configuration. The simulation results are compared with the experiments at two configurations in terms of sound pressure spectrum, and the pressure fluctuation leading to the tone noise and the corresponding unsteady flow phenomenon are discussed to clarify the noise generation mechanism. A feedback loop is formed between the vortex shedding from separated blade surface boundary layer and the resulting aerodynamic sound at the trailing edge, which results in the tone noise.